Pementasan Drama dalam Pembelajaran Perguruan Tinggi: Telaah Terhadap Unsur Kelengkapan Artistik dan Akting - Anisa, Risma; Syukriady, Dwi; Erniati, Erniati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2026)
Drama performance learning in higher education tends to focus primarily on stage performance, while conceptual understanding of performance elements, artistic completeness, and acting skills has not been comprehensively explored by students. This study aims to analyze the fundamental principles of drama performance in higher education learning by emphasizing performance elements, artistic aspects, and acting. The study employs a qualitative approach using a descriptive-analytical method through a literature review of relevant scholarly journals and academic references related to drama performance. The results indicate that performance elements such as script, director, actors, dialogue, and conflict play an essential role in constructing a coherent and communicative dramatic performance. In addition, artistic elements—including stage setting, make-up, costumes, lighting, music, and properties—serve to strengthen the dramatic atmosphere and aesthetic value of the performance. Acting, on the other hand, becomes the core of drama performance as actors convey ideas, emotions, and dramatic messages through character interpretation and expression. Therefore, a comprehensive understanding of performance elements, artistic components, and acting should be emphasized in drama learning so that students are not only capable of presenting technical performances but also understand the conceptual foundation and creative process underlying drama performance.